Gambaran Organismic Involvement dan Self Regulation pada Aktor Teater yang Pernah Mendapatkan Penghargaan atau Pengakuan dari Lembaga Pemerintah - Annisa Putri Ayudya; Sri Rochani Soesetio; Nathanael Elnadus J. Simampouw (Jurnal Ilmiah Psikologi MIND SET, 2010)
The study aims to examine the organismic involvement and self regulation on stage actors who receive awards or acknowledgment from a government institution. Organismic involvement is an imagination which is inspired by a narration affecting an actor's belief and act on the stage (Daiute & Lightfoot, 2004). Self regulations is an ability to develop, implement and regulate a planned behavior in a flexible way to achieve a desired future outcome. This is a qualitative study based on general interviews. The subjects are two main actors and two supporting actors, each from traditional theaters and modern theaters. The finding refers to Sarbin's role theory (1954) that the third level of organismic involvement is the best level for role play on stage. The two respondents who received an award or acknowledgment from the goverment institution have also reached level three. An individual should better achieve level four which involve more learning process to gain optimal therapy and intervention process. Besides, acting skills, talent, emphaty and self regulation are required in the process to achieve an excellent role play on the stage.